2015
DOI: 10.1108/ijse-09-2013-0208
|View full text |Cite
|
Sign up to set email alerts
|

Financial development and income inequality in India: an application of ARDL approach

Abstract: Purpose – The purpose of this paper is to examine the relationship between financial development and income inequality in India using annual data from 1982-2012. Design/methodology/approach – Stationarity properties of the series are checked by using ADF, DF-GLS, KPSS and Ng- Perron unit root tests. The paper applied the auto regressive distributed lag (ARDL) bound testing approach to co-integration to examine the existence of long run r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 55 publications
(58 reference statements)
7
42
0
5
Order By: Relevance
“…and other nancial services are enjoyed by the wealthy strata of the society. These results are consistent with the ndings of existing literature Jauch and Watzka (2016), Koh et al (2020), Sehrawat and Giri (2015) and Seven and Coskun (2016) but contradictory with the ndings of Kapingura (2017) and Omarand Inaba (2020) who report that access to nancial services and strong nancial inclusion alleviate income inequality signi cantly. To capture the nonlinearities, if any, and to explore thse presence of the GJ hypothesis (1990), the squared term of nancial development (FD 2 ) is used in the Eq.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…and other nancial services are enjoyed by the wealthy strata of the society. These results are consistent with the ndings of existing literature Jauch and Watzka (2016), Koh et al (2020), Sehrawat and Giri (2015) and Seven and Coskun (2016) but contradictory with the ndings of Kapingura (2017) and Omarand Inaba (2020) who report that access to nancial services and strong nancial inclusion alleviate income inequality signi cantly. To capture the nonlinearities, if any, and to explore thse presence of the GJ hypothesis (1990), the squared term of nancial development (FD 2 ) is used in the Eq.…”
Section: Resultssupporting
confidence: 82%
“…Rubin and Segal (2015), Sehrawat and Giri (2015) and Shari (2000). and other nancial services are enjoyed by the wealthy strata of the society.…”
Section: Resultsmentioning
confidence: 99%
“…One important finding-from all models except Model H-is that while we take both financial size and efficiency separately into estimation, the two variables appear to increase the Gini coefficient, that is, the expiation and amelioration of the financial system are significant to exacerbate India"s income inequality. This result agrees with Bahmani-Oskooee and Zhang (2015) and Sehrawat and Giri (2015) but does not with Ang (2010) who confirmed the inequality-reducing effect of financial development. Furthermore, with no evidence of the nonlinear effect of financial depth on income distribution, we also discovered that India"s financial system is not releasing the distributional effect as Greenwood and Jovanovic (1990) expected.…”
Section: Resultssupporting
confidence: 78%
“…The authors found that financial development increases income inequality after having controlled for fixed effects by country and possible endogeneity prob-lems. Likewise, Sehrawat and Giri (2015) studied the link between finance and inequality in India for the period 1982 to 2012, suggesting that financial development exacerbates income inequality both in the long and short term. In turn, Rajan (2010) -based on a model of Kumhof and Ranciere (2011) -found that individuals with incomes in lower deciles borrow to increase their consumption more than do those with stagnant incomes.…”
Section: Empirical Review Banking Sector and Income Inequalitymentioning
confidence: 99%